Educating Medical Students on How to Prescribe Anti-Hyperglycaemic Drugs: A Practical Guide - Erik M. Donker; Andrej Belančić; Joost D. Piët; Dinko Vitezić; Jelle Tichelaar; on behalf of the Clinical Pharmacology and Therapeutics Teach the Teacher (CP4T) Program and the Early Career Pharmacologists of the European Association for Clinical Pharmacology and Therapeutics (EACPT) (Diabetology, 2023)
In the light of the rapidly increasing global incidence of, and therapeutic arsenal for, diabetes type 2, this brief report underscores the need for advancements in clinical pharmacology and therapeutics (CPT) education with regard to diabetes type 2. We advocate for the comprehensive training of medical students and junior doctors in line with current guidelines, and emphasize the importance of teaching how to draw up individualized treatment plans based on patients’ specific risk factors and conditions, such as cardiovascular risks, weight, and risk of hypoglycaemia. Within the curriculum, traditional teaching approaches should be replaced by innovative methods such as problem-based learning, which has been shown to be more effective in developing prescribing knowledge and skills. The inclusion of real-world experience and interprofessional learning via so-called student-run clinics is also recommended. Subsequently, innovative assessment methods like the European Prescribing Exam and objective structured clinical examinations (OSCE) are highlighted as essential for evaluating knowledge and practical skills. By adopting these educational advances, medical education can better equip future practitioners to adequately manage the complex pharmacological treatment of diabetes.